“ATTEND TO THYSELF:” ATTENTIVENESS AND DIGITAL CULTURE - CONSTAS, Maximos (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2023)
The rise of digital culture has created both tremendous human possibilities as well as tremendous challenges and problems. Powerful corporate and commercial interests compete for our attention, which has become a valuable commodity in the online world. Living in a culture of organized distractions, human awareness is fragmented, causing us to lose touch with ourselves, our neighbors, the world around us, and God. This paper explores the traditional ascetic practice of attention and watchfulness which it recommends as a counterweight to modern cultural, psychological, and spiritual fragmentation. The principal sources under consideration are drawn from the Philokalia, a collection of writings devoted to the practice of attending to oneself.